Legal Protection of Ikat-Pahikung Woven Fabric Motifs in East Sumba Regency - Rambu Susanti Mila Maramba; Rambu Hada Indah; Pajaru Lombu (Jurnal Hukum Volkgeist, 2021)
Ikat weaving has been a source of employment, an important livelihood for the family and is widely recognized for a long time. One of the problems, in the last five years, has been the influx of "fake" ikat and even ikat textiles from outside East Sumba, which increasingly pushes the original ikat on the island of Sumba. There have been many "imitation" ikat weavings that use the original Sumba motif from the island of Java, forexample; Jepara, Pekalongan, Klaten, and other weaving clusters on the island of Java. This fact has implications for issues of performance, competitiveness, and sustainability of the ikat industry in East Sumba Regency which greatly impacts on the sources of employment and livelihoods of the local community. Therefore, this research will analyze the legal protection of the ikat-pahikung woven fabric motif in East Sumba Regency. This research is conducted by using field research (Empirical Research), which is to go directly to the field to conduct research using the Legal Sociology Approach, which is to examine and understand social phenomena in society to see the existing legal facts.